2018
DOI: 10.1016/j.ecoser.2018.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Conceptual advancement of socio-ecological modelling of ecosystem services for re-evaluating Brownfield land

Abstract: Essential environmental resources are rapidly exploited globally, while socialecological systems at different scales fail to meet sustainable development challenges. Ecosystem services research, which at present predominantly utilizes static modelling approaches, needs better integration with socio-economic dynamics in order to assist a scientific approach to sustainability. This article focuses on Brownfield lands, a unique landscape that is undergoing transformations and provides ecosystem services that rema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 111 publications
(109 reference statements)
0
24
0
1
Order By: Relevance
“…A recent review of studies that have modelled interactions between multiple ES found that a large proportion did so from the perspective of co-occurring production synergies and trade-offs, but that the examination of flows, and the identification and quantification of explicit functional relationships remain largely unexplored (Agudelo et al 2020). Ultimately, simultaneously modelling multiple ES continues to be difficult in part because of methodological inadequacies and the complexity of the ecological processes involved (Kolosz et al 2018). Our approach provides a new framework that can help address these challenges.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent review of studies that have modelled interactions between multiple ES found that a large proportion did so from the perspective of co-occurring production synergies and trade-offs, but that the examination of flows, and the identification and quantification of explicit functional relationships remain largely unexplored (Agudelo et al 2020). Ultimately, simultaneously modelling multiple ES continues to be difficult in part because of methodological inadequacies and the complexity of the ecological processes involved (Kolosz et al 2018). Our approach provides a new framework that can help address these challenges.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we are limited in the generalizations we can make, especially as they pertain to the specific locations, LULC- and ecosystem-relevance of the potential for connectivity ‘hotspots’. Investigating a limited number of ES is common among studies that model interactions among ES (Agudelo et al 2020), with data limitations, complexity of socio-ecological process involved, and methodological gaps cited as barriers to inclusion of all ES (Kolosz et al 2018). However, our choice to test only three ES was motivated by our goal to provide a straightforward case study of how each of the three broad ES categories (i.e., non ‘supporting’; MEA 2005) can be represented in the same study.…”
Section: Appendicesmentioning
confidence: 99%
See 1 more Smart Citation
“…There is often no real valid relation between spot-oriented sampling or monitoring regarding up-scaling approaches to regional or global scales, but vice versa, also no real attempts to down-scale and validate outcomes from global assessments and modelling approaches with regard to their local reliability (e.g. Kolosz et al 2018;Le Clec'h et al 2018;Malenovský et al 2019). Most of the modelling approaches in land use sciences are purely data driven and miss making use of such theoretical frameworks as provided by the socialecological system concept (Colding and Barthel 2019).…”
Section: Challenges In Research Practicementioning
confidence: 99%
“…In addition, based on another laboratory study, Kim and Lee [81] observed maximum CO 2 sequestration capacity of 195 kg for one tonne of bottom ash. If the 6.8 and 1.7 million tonnes of fly and bottom ashes, respectively, being produced annually in Malaysia [73] would be used for the first 10 cm of land associated with the country's future developments (e.g., using lands associated with construction of highway [14,82]), more than 9000 ha of land could be designed for inorganic CO 2 sequestration, and 500,000 tonnes of CO 2 could be captured. This figure accounts for 0.2% of the country's projected total CO 2 emission in 2020.…”
Section: Malaysia's Capacity For Using Soil Mineral Carbonationmentioning
confidence: 99%